Pandangan Dunia Pengarang dalam Novel Bulan Terbelah di Langit Amerika Karya Hanum Salsabiela Rais dan Rangga Almahendra serta Implikasinya dalam Pengajaran Sastra - Effendi, Darwin; Hetilaniar, Hetilaniar (UNIB Press, 2019)
The purpose of this study was to gain an in-depth understanding of the author's worldview in the novel Bulan Terbelah di Langit Amerika by Hanum Salsabiela Rais and Rangga Almahendra and the implication in teaching literature. This qualitative research uses the content analysis method through a structural genetic approach. Data collection using library study techniques. The validity of the data to get the credibility of the data is used triangulation techniques. Based on the results of the study showed that the author's worldview represents his group of beliefs that are disturbed by the negative views of other groups that are not the same as their beliefs. The picture of the life of the American social community through stories has inspired the author about how to convey Islam correctly to people who do not understand it. As Muslims, they are obliged to defend the truth of Islam that has been misinterpreted. The author's worldview also confirms that due to terrorist acts in the name of Islam, non-Muslim communities criticize it and always blame Moslem.